Improving Learners’ Motivation and ELT Achievement through Discovery Learning Model after the Covid-19 Pandemic - Andi Masani (Journal of Languages and Language Teaching, 2022)
The discovery learning model has several advantages when compared to other learning models such as that learners are involved in collaboration with peer classmates and with teachers. The activities can bring students to create a sense of pleasure and enthusiasm because they can directly investigate and find out the results. This study was aiming at improving learners’ motivation and ELT achievement of the seventh-grade learners after Covid-19 Pandemic through the application of a scientific approach using Discovery Learning model. This study is a Classroom Action Research (CAR). The study was conducted at SMP 4 Mataram involving 16 learners. This research was carried out in two cycles. The research procedure consisted of planning, implementation, observation and reflection. The observation sheets, student observation sheets, motivation questionnaires and ELT tests were employed to gain the research data. The data were analyzed in descriptive ways. The results of the study in the first cycle showed that the average score for teacher activities was 3.18, learner activities were 3.38, individual assignments were 68.25, and written tests were 67.69. Those were incomplete category. Furthermore, in the second cycle, the average score for teacher activities was 4.43, learner activities were 4.21, individual assignments were 80.88, and written tests were 84.31. These were included in the complete category. These results indicate that the indicators of success (> 4.0) and ELT achievement (> 75.00) have been exceeded. Because the indicators of success have been achieved, the study is declared successful. It means that the use of discovery learning is able to improve learners’ motivation and ELT achievement after Covid-19 pandemic.